Heterogeneity in mixed economies: Implications for sensitivity and adaptive capacity. Issue 4 (April 2019) - BurnSilver, Shauna; Magdanz, James
Abstract : In a 'mixed economy', households embedded in communities simultaneously engage in the cash economy, pursue some aspect of subsistence, and remain connected to each other through a culturally rich set of sharing and cooperative relationships. In Alaska and the circumpolar north, mixed economies show signs of persistence despite significant challenges, and have become a cultural touchstone for what it means in the present day to be, for example, Iñupiat or Gwich'in. Contemporary research on mixed economies highlights common patterns, such as the role of cash in sustaining subsistence, and the importance of 'super-households' in food production and distribution. However, similarities at the community level can obscure important differences at the household level. Combining concepts of sensitivity and adaptive capacity drawn from vulnerability literature, this paper explores differences in household characteristics within and between three Alaska communities. Two communities are coastal Iñupiat (Wainwright and Kaktovik), and one is interior Gwich'in (Venetie). Findings illustrate significant heterogeneity in households' livelihood strategies, capabilities and available assets. Differences within and between communities suggest areas of emerging inequality relevant to ongoing discussions of well-being and sustainability across a changing circumpolar north.